(untitled) (RIVISTA ITALIANA DI PALEONTOLOGIA E STRATIGRAFIA, 2006)
New stratigraphic data (exposed sections and boreholes) allowed a detailed reconstruction of the northern sector of the "Terrazzo di Livorno" (Central Italy). A new unit, called "Corea formation" was discovered and correlated to marine isotope stage (MIS) 6 and to its transition to MIS 5. This formation comprises, at its base, fluvial gravels and sands followed by fine-grained alluvial plain deposits. Non-marine molluscs, small mammals and pollen allow a reconstruction of the environment present during the deposition of the alluvial plain deposits. The environment was mainly an open space, though sparse woodlands should have been present. The non-marine fauna shows features intermediate between typical interglacial and glacial assemblages described so far in Italy. Worth of note is the presence of Orcula dolium and Vallonia enniensis, which now inhabit northern Italy. These findings improve our knowledge on the biogeography of Quaternary non-marine faunas of Central Italy. Stable isotopes data on land snail shells, freshwater shells and pedogenic carbonates showed that climate conditions were cooler than today (possibly 1-2°C less) with a significant amount of C4 vegetation, in an environment with moderately dry conditions.